Testicular Feminization or Androgen Insensitivity Syndrome (AIS) in Iran: a Retrospective Analysis of 30-Year Data - Dariush. D FARHUD; Marjan ZARIF YEGANEH; Hosein SADIGHI; Shahram ZANDVAKILI (Tehran University of Medical Sciences, 2016)
Background: Androgen insensitivity syndrome (AIS) or testicular feminization is a partial or complete inability of cell response to androgen. The cause is enzymatic defect in synthesis of testosterone, resulting sexually immature phenotypically female, with primary amenorrhea. There are three categories of AIS, complete, partial and mild, depending on the degree of external genital masculinization. The aim of this study was to find out chromosomal abnormalities, and correlation between AIS and maternal/paternal age, parents' consanguineous marriage, family history and clinical observation, in Iranian AIS patients.   Method: This study includes a retrospective data analysis of 72,000 families' medical records in the Genetic Clinic in Tehran, during a 30-yr period (1984-2014). The essential basis for the patients' referral to the clinic by gynecologists was primary amenorrhea. Cytogenetic abnormalities has been confirmed by chromosome G-banding and conventional staining methods. Results: Seventy AIS female patients with 46XY pattern were cytogenetically diagnosed and the frequency of AIS syndrome was estimated about 0.05% (~70/140000). The results showed no association between AIS and maternal or paternal age nor were the marital pattern of the parents. The clinical findings illustrated that primary amenorrhea had the highest indication for referral of AIS patients for genetic counseling and cytogenetic study. Conclusion: No correlation was observed between AIS and maternal or paternal age or consanguineous marriages. Amenorrhea is the most clinically observed sign of AIS patients.   Keywords: Androgen insensitivity syndrome (AIS), Testicular feminization, Human androgen receptor (HAR), Amenorrhea, Iran